Rhodium‐Catalyzed Cascade Synthesis of Benzofuranylmethylidene‐Benzoxasiloles: Elucidating Reaction Mechanism and Efficient Solid‐State Fluorescence. Issue 28 (10th April 2018) - Namba, Tomoya; Hayashi, Yoshihiro; Kawauchi, Susumu; Shibata, Yu; Tanaka, Ken
Abstract: A new synthetic route to highly fluorescent benzofuranylmethylidenebenzoxasiloles through cationic rhodium(I)/binap complex‐catalyzed cascade cycloisomerization of bis(2‐ethynylphenol)silanes has been developed involving 1, 2‐silicon and 1, 3‐carbon (alkyne) migrations followed by oxycyclization. The present synthesis requires only three steps, starting from commercially available dichlorodiisopropylsilane, which is markedly shorter than our previous synthesis (eight steps starting from commercially available chlorodiisopropylsilane). Theoretical calculations elucidated the mechanism of the above cascade cycloisomerization. This reaction is initiated by the formation of a rhodium vinylidene not through direct 1, 2‐silicon migration but rather through an unprecedented stepwise 1, 5‐silicon migration followed by C−Si bond‐forming cyclization from a dearomatized allenylrhodium complex. Subsequent 1, 3‐carbon (alkyne) migration leading to a η 3 ‐allenyl/propargyl‐rhodium complex followed by oxycyclization through π‐bond (alkyne) activation with the cationic rhodium(I) complex affords the benzofuranylmethylidenebenzoxasilole product. The structure–fluorescence property relationships of the thus obtained benzofuranylmethylidenebenzoxasiloles were investigated, which revealed that good fluorescence quantum yields were generated in the solution state ( φ F =69–87 %) by introduction of electron‐donating alkyl and phenyl groups on two phenoxy groups. In the powder state, 4‐methyl‐ and 4‐methoxy‐phenoxy derivatives exhibited efficient blue fluorescence ( φ F =52 % and 46 %, respectively). Especially, the 4‐methylphenoxy derivative was thermally stable, and exhibited strong narrow‐band fluorescence in the film state (blue, φ F =95 %) and redshifted strong narrow‐band fluorescence (green, φ F =90 %) in the crystalline state as a result of the formation of an offset π‐stacked dimer; the latter was confirmed by X‐ray crystallographic analysis and by theoretical calculations. Abstract : Let it glow ! A new three‐step route to highly fluorescent benzofuranylmethylidenebenzoxasiloles through cationic rhodium(I) complex‐catalyzed cascade cycloisomerization of bis(2‐ethynylphenol)silanes has been developed. The thus obtained benzofuranylmethylidenebenzoxasiloles were highly emissive, with the 4‐methylphenoxy derivative exhibiting strong narrow‐band fluorescence in the film state (blue, φ F =95 %) arising from the monomer and redshifted strong narrow‐band fluorescence in the crystal state (green, φ F =90 %) arising from formation of an offset π‐stacked dimer.